Transformational leadership: A critical approach of knowledge and talent management for lecturer performance - Nurmadhani Fitri Suyuthi; Andi Farisnah Anwar; Ilham Safar; Fakhruddin Kurnia M; Wahyu Wahyu (Journal of Innovation in Business and Economics, 2025)
This study aims to examine the influence of Knowledge Management (KM), Talent Management (TM), and Transformational Leadership (TL) on the performance of higher education institutions in Makassar, Indonesia, emphasizing the role of TL as a mediator between KM and TM and institutional performance. This quantitative study involved 325 lecturers from various universities in Makassar. Data were analyzed using Structural Equation Modeling (SEM) to assess the relationship between KM, TM, TL, and lecturer performance. The results showed that KM and TM have a significant positive influence on performance, both directly and through the mediation of TL. KM positively affects TL, and these two variables, along with TM, contribute significantly to performance improvement. However, the interaction between KM and TL did not show a significant moderating effect on performance, indicating that the direct influence of KM and TM is more dominant in this context. This study confirms the importance of the integration of KM and TM in improving the performance of higher education institutions and demonstrates the strategic role of TL in maximizing the effectiveness of these management strategies. The findings suggest that effective leadership can enhance the implementation of KM and TM, which overall improves organizational performance. The practical implications of this study are highly relevant for policy makers and university administrators in Makassar to develop and implement strategies that integrate effective KM and TM practices, directed by transformational leadership. Further research is recommended to use a longitudinal design to validate the findings and understand the dynamics of this relationship over time.